THEORETICAL ASPECTS OF MANAGEMENT OF INTELLECTUALIZATION OF ENTERPRISE ACTIVITIES IN THE CONDITIONS OF DIGITIZATION (INNOVATIVE ECONOMY, 2025)
Boіchyk V.Ye., Sobko O.M.  THEORETICAL ASPECTS OF MANAGEMENT OF INTELLECTUALIZATION OF ENTERPRISE ACTIVITIES IN THE CONDITIONS OF DIGITIZATIONPurpose. The aim of the article is to study the theoretical aspects of managing the intellectualization of an enterprise's activities and substantiate its role in the formation of intellectual capital and ensuring the competitiveness of an enterprise.Methodology of research. The following research methods were used to achieve the set goal, as particular: scientific generalization and systematization, analysis and synthesis, logical abstraction and comparison, which made it possible to specify the conceptual and categorical apparatus of intellectualization of the enterprise's activity and to substantiate the cause-and-effect relationships between intellectualization and intellectual capital.Findings. The theoretical essence of the intellectualization of enterprise activity as a dynamic process of increasing the role of knowledge, intellectual work, innovations and digital technologies in shaping the results of economic activity is revealed. The cause-and-effect relationship between the intellectualization of activity and the formation of intellectual capital of the enterprise is substantiated, according to which intellectualization is the primary process, and intellectual capital is the result and at the same time a factor in the further development of this process. The content of technological knowledge and technological assets of knowledge is clarified; their differences and role in the structure of intellectual capital are defined. It is shown that technological knowledge assets are formed in the process of transforming technological knowledge from an implicit and personified form into a formalized and economically significant one. The importance of cognitive knowledge in the processes of intellectualization of the company's activity is determined, in particular in the context of the formation of mental models, management practices and improving the quality of management decisions. The role of digitization as a factor in accelerating the intellectualization of activity and effective use of the enterprise's intellectual capital is substantiated.Originality. The author's approach to the interpretation of the intellectualization of the company's activity as a process of transformation of cognitive knowledge and technological assets of knowledge into integrated intellectual capital, which is formed in conditions of digitalization, is substantiated. Practical value. The obtained results can be used in the process of managing the intellectualization of enterprise activities, in particular, in the formation and development of intellectual capital, improving the knowledge management system, and making managerial decisions in the conditions of the digital economy.Key words: intellectualization, intellectualization of enterprise activity, intellectual capital, cognitive knowledge, technological assets of knowledge, digitalization, management, intellectualization management, knowledge management.
Keywords: intellectualization; intellectualization of enterprise activity; intellectual capital; cognitive knowledge; technological assets of knowledge; digitalization; management; intellectualization management; knowledge management